The effect of Shirodhara on essential hypertension: Systematic review and meta-analysis - Meenakshi Khapre; Dhanlika Dhanlika; Sriloy Mohanty; Amrita Mehndiratta (Journal of Education and Health Promotion)
Essential hypertension, a common multifactorial condition, is a significant public health concern. In India, the prevalence of hypertension is high, with estimates indicating a rising trend. Shirodhara, an Ayurvedic therapy, has exhibited the potential for stress reduction and relaxation. Thus, the review investigates the effect of Shirodhara on systolic and diastolic blood pressure and its impact on clinical symptoms like palpitation, insomnia, giddiness, fatigue, and headache in essential hypertensive patients. We searched PubMed, Embase, Scopus, Google Scholar, and Shodhganga, Web of Science search for this systematic review and meta-analysis from inception to June 2023. Evidence from RCTs was synthesized as a standardized mean difference (SMDs) for systolic and diastolic blood pressure, comparing participants who received Shirodhara intervention along with Ayurveda medication and those who received only Ayurveda medication. The Revised Cochrane Risk of Bias tool for randomized control trials (RoB-2) was used for the quality assessment of randomized control trials. Analysis was done using Medcalc software. The comparison table is provided for the percentage of relief in clinical symptoms in both groups. Out of four RCTs, only three were included for quantitative analysis, which mentioned the mean and standard deviation of systolic and diastolic blood pressure. Meta-analyses revealed the effects of Shirodhara on systolic blood pressure (n = 100), the mean difference (MD) was − 1.257 mmHg, (2.660–0.145), I2 = 89.3%, and diastolic blood pressure (n = 100) MD was − 0.40 mmHg, (−0.79–0.01) I2 = 0. The percentage of relief in clinical symptoms was notably higher in the Shirodhara and Ayurveda groups than in the Ayurvedic drug group. Shirodhara lowered diastolic blood pressure significantly, but it has low clinical value. Shirodhara’s effect on systolic blood pressure remained unclear. Relief in clinical symptom score was notable. Larger, well-designed research is needed to prove Shirodhara’s effectiveness in hypertension management and optimize therapy methods.